Assuring adequate deterrence in tort: A public good experiment - Theodore Eisenberg; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2012)
To explore damage rules' deterrent effect, we use a public good experiment to tailor allowable punishment to rules used in actual civil litigation. The experimental treatments are analogous to: (1) damages limited to harm to an individual litigant, (2) damages limited to harm to a group available in aggregate litigation, such as class actions, and (3) damages allowed beyond actual harm to victims, such as punitive damages. The treatment with damages limited to harm to an individual does not prevent the deterioration in cooperation over time commonly found in public good experiments without punishment or with too low punishment. In the class action damages treatment, cooperation is stable over time. In the damages-beyond-harm treatment, cooperation approaches the optimal level, but concerns of socially unjust punishment arise. In all treatments, a money maximising agent would be expected to completely freeride and make no contribution to the public good. Our results can thus not be explained by an incentive effect. Rather we find that social preferences interact with the severity of sanctions, even if imposing the sanction is not altruistic, but instead financially benefits the sanctioning authority. The results persist in a variation of the three treatments in which the player imposing damages has the option to not retain them for herself but to have them forfeited with no benefit to her. We can therefore rule out that the beneficial effect of sanctions hinges on the participants knowing that the player imposing sanctions cannot intend to enrich herself. The methodology we develop could be used to assess the social welfare benefit of many damages rules, such as treble damages in antitrust cases and caps on damages common in medical malpractice cases and punitive damages cases.
Keywords: K13; K4; C73; K0; 330; Deterrence; Public Good Experiment; Class actions; Tort; Damages; Punitive damages